Salesperson Capability on Co-Creation Value - Marlien, R. A.; Alimaskur, Alimaskur; Setiawan, Mulyobudi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2017)
This research focuses on the study of customer engagement in planning and deciding on products and services to be purchased through the salesperson. This is a study of the relationships between firms and customers based on collaboration theory, customer value, relationship marketing and resource-base view (RbV). the development of information technology causes the company to change the paradigm to become customer-centric. Customers are actively involved in creating value that suits the desired and customer experience. Financial services such as insurance is required to establish cooperation or strong collaboration so that both companies and customers get the expected benefits. The method used to analyze the model is multiple regression with a sample of 100 respondents in the life insurance company customers in Semarang. Sampling technique using purposive sampling. The co-creation value formed from collaborative values, customer perceptions and customer participation with the salesperson capability mediated generates unique co-creation values in accordance with customer wants and needs.